Musiken som förändringskraft: Manifest för aktivistisk musikforskning - Susanna Välimäki; Sini Mononen; Kaj Ahlsved (Tutkimusyhdistys Suoni ry, 2022)
Musiken som förändringskraft presenterar utgångspunkter för aktivistisk musikforskning. Ur ett samhälls- och miljöperspektiv kräver 2000-talets krisvärld aktiv, ställningstagande och förändringsinriktad forskning. Samtidigt skär staten ner finansieringen för utbildning, universitet och forskning. Hur bemöter musikvetare de här utmaningarna? Forskningsföreningen Suoni rf bedriver aktivistisk och obunden musikforskning. I boken reflekterar föreningens medlemmar över sitt samhällsorienterade forskarskap och presenterar möjligheter för samhälleling och praxisorienterad musikforskning i den finländska musikkulturen. Bokens författare är musikforskare som utöver sitt forskarskap bl.a. verkar som fria författare, kritiker, radio- och tv-producenter, föreningsaktiva, lärare, dj:n, miljöaktivister och i många andra roller knutna till folkbildning, publikarbete och sakkunniguppdrag. De förenas av en vilja att studera verkligheten genom musik, att arbeta för rättvisa musikaliska praktiker och genom musikforskning kämpa för en bättre värld.
ENGLISH ABSTRACT: Music as a Tool for Social Change outlines starting points for activist, i.e., societally critical, praxis oriented and rebellious music research. The risk society and world of crises in the 21st century require activist research that examines the questions of social and environmental justice and aims for social change. At the same time, the funding for education, universities and research are constantly cut. How do musicologists respond to these challenges? The members of the independent Research Society Suoni (ry) reflect their ideas about and plans for activist music research. The authors of the book are Finnish music researchers who in addition to their work as researchers, and as linked to that, work as free authors, music and art critics, radio and TV program producers, teachers, DJs, environmental activists, and in other expert positions related to music and arts, public education, audience development, and civil activism. The authors share a desire to study reality via music, to transform musical practices socially and environmentally more just and sustainable, and to fight for a better world with music and music research. The book has been published originally in Finnish as Musiikki muutosvoimana: Aktivistisen musiikintutkimuksen manifesti
Contents: (1) Susanna Välimäki, Juha Torvinen & Sini Mononen: Introduction: Activist music research //
(2) Sini Mononen: Researcher-critic: Art criticism as activism //
(3) Susanna Välimäki: Researcher in radio and television: How and why talk to people about music? //
(4) Kim Ramstedt: Researcher-dj as a cultural mediator: Music and the promotion of equality //
(5) Susanna Välimäki: Researcher at festivals and orchestras: Audience development, societal activism and critical thinking //
(6) Saijaleena Rantanen: Researcher as a history teller: Whose music are we talking about? //
(7) Juha Torvinen: Researcher as an environmental activist: Theses on music researcher's relation to nature //
(8) Kaj Ahlsved: Researcher as media actor, public educator and music pedagogue: Prospects and challenges of social responsibility //
(9) Sini Mononen: Researcher-actor: Praxis oriented institutional criticism //
(10) Sini Mononen & Susanna Välimäki: The ABC of activist music research